THE PECULIARITIES OF BUDGETARY FINANCING THE PUBLIC GOODS PRODUCTION IN THE EUROPEAN UNION COUNTRIES: THE LESSONS OF POLAND FOR UKRAINE - Marianna Kichurchak (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The peculiarities of distribution and use of budgetary facilities for the public goods production in the EU countries, including Poland, are considered and possibilities of adaptation of this experience to the Ukrainian conditions are determined in the article. The author has made the comparative analysis of the structure of general budgetary expenditures in the EU countries and Ukraine, revealed the regularities of financing the public goods production on the basis of calculating the elasticity of general budgetary expenditures by function to GDP, the index of the structure change in general budgetary expenditures and implementing the cluster analysis, and suggested certain recommendations concerning the improvement of financing public goods production in Ukrainian economy taking into account euro–integration aspirations.